AB0208 Reduced Hand Function Indicates Higher Disease Activity In Patients With Rheumatoid And Psoriatic Arthritis - Coppers, Birte; Heinrich, Simon; Bayat, Sara; Tascilar, Koray; Kleyer, Arnd; Simon, David; Minopoulou, Ioanna; Corte, Giulia; Fagni, Filippo; Schönau, Verena; Bohr, Daniela; Leyendecker, Sigrid; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Measuring disease activity in patients with inflammatory arthritis remains challenging and is mainly based on physician-dependent assessments, subjective measures and just one blood biomarker of inflammation with no indication of the subclinical or functional state of the patients [1, 2]. Patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA) present with impaired hand function compared to healthy controls [3, 4]. While hand function is well studied in RA patients [5], data is sparse for PsA patients. Objectives: To employ the association between clinical disease activity scores and objectively measured hand function impairment in RA and PsA patients. Methods: Three conventional hand function tests were performed by PsA (CASPAR criteria) and RA (ACR/EULAR 2010 criteria) patients (Internal Medicine 3 outpatient clinics Erlangen, Germany) and healthy controls (HC) (study: Ethics #357_20B, DRKS00032490). The clinically assessed disease activity scores (Disease Activity in Psoriatic Arthritis Score (DAPSA) [1], Disease Activity Score 28 (DAS28) [2]) and the best trial for each of the hand function tests were used for this analysis: the highest out of three trials for an isometric grip strength test (Dynamometer, Saehan, Korea, Figure 1 A), the highest out of two trials for a dynamic grip strength test (Martin Vigorimeter, Germany, Figure 1 B) and the fastest out of two trials for the fine motor skill Moberg Picking-Up Test (MPUT) (Figure 1 C) for each hand. Mixed-effect linear regression models adjusted for age were used to employ the associations between the clinical disease activity scores and hand function tests of the patients. Analyses were stratified by sex. Results: We included 76 PsA patients (37 male, 52.0±4.3 years; DAPSA: 10.2±7.1), 73 RA patients (24 male, 53.9±14.1 years; DAS28: 2.6±0.9), and 77 HC (37 male, 46.0±18.5 years) in this study. For RA patients one-unit increase of the DAS28 was significantly associated with reduced dynamic grip strength for both sexes (Table 1, p<0.05) but not with a reduced isometric grip strength. Performance time of the MPUT was on average 11% (male) and 7% (female) longer with one-unit increase in the DAS28 score, but was not statistically significant. In PsA patients, a one-unit increase in the DAPSA score was associated with worse hand function on all measurements, but these were significant only in male patients (all p<0.05, Table 1). The MPUT showed worse performance of 2% in males and 1% in females for each one-point increase of the DAPSA score. Conclusion: Increased disease activity is associated with reduced hand function in PsA and RA patients. The dynamic grip strength test (vigorimeter) seems to be more sensitive than the isometric grip strength test (dynamometer) to detect functional changes in relation to disease activity. For male PsA patients, the fine motor MPUT may be particularly suitable to reflect changes in disease activity. Longitudinal properties of these measurements, such as sensitivity to change, need to be further explored. An overall low disease activity in PsA and RA patients is a limitation of our stud

AB0929 THE IMPACT OF KINESIOPHOBIA ON GAIT KINEMATICS IN PATIENTS WITH SPONDYLOARTHROPATHIES - Schweiger, Isabella; Koschinsky, J.; Elie-Tino, Godonou; Tascilar, Koray; Coppers, Birte; Kleyer, Arnd; Morf, Harriet; Simon, David; Bayat, Sara; Bohr, Daniela; Valor, L.; Raimondo, Maria Gabriella; et al. (Annals of the Rheumatic Diseases, 2024)
Background: In light of much needed functional assessments to monitor disease activity and functional status in spondyloarthritis (SpA), gait analysis is gaining interest. While it is generally known that the functional status and gait kinematics are closely related, it is unclear how fear of movement (kinesiophobia) affects gait kinematics in SpA patients. Objectives: To assess the influence of kinesiophobia on gait kinematics in patients with SpA and how sex mediates this relationship. Methods: A standardized 2-minute walk with self-selected walking speed was performed with 104 patients (psoriatic arthritis (PsA, CASPAR criteria) and ankylosing spondylitis (axSpa, ASAS criteria) (Internal Medicine 3 outpatient clinics Erlangen, Germany) in the hospital hallway. Spatio-temporal gait parameters (number of analyzed steps, cadence, gait velocity, double stance length and duration, swing left and right, stance left and right, temporal and spatial gait cycle variability) were recorded using the inertial sensor system RehaGait® (Hasomed, Magdeburg, Germany) and sagittal joint angles were computed and analyzed via MATLAB [1] (of the whole gait cycle the maximal and minimal flexion angle of left and right hip, knee, ankle). Patient characteristics and clinical assessments were retrieved from the patients record on the day of the gait analysis. Additionally, patients were asked to fill out the tampa scale of kinesiophobia (TSK) and an anamnestic questionnaire. Multivariate multiple linear regression was used to investigate the relationship between TSK score and kinematic gait parameters; mediation analysis was computed with sex as the control variable (potential mediator). Results: Patients characteristics of the 104 participants in this study are summarized in Table 1. Kinesiophobia affected the mediator sex (0.039; CI (0.005, 0.074), p=0.026) and the effect of kinesiophobia on gait kinematics differs between sexes. When controlling for the TSK score, male subjects took fewer steps and had a longer stance length. This may be due to them being taller (female: 166.6 cm, male: 179.9 cm; p<0.001). When controlling for sex, kinesiophobia is significantly associated with gait velocity (Coef: -0.009, p=0.003), double stance length (Coef: -0.005, p=0.031), double stance duration (Coef: 0.004, p=0.007), cadence (Coef: -0.39, p=0.006), swing phase left (Coef: -0.089, p=0.006) and the minimal left knee angle (Coef: -0.002, p=0.046). Conclusion: Patients with higher fear of movement scores by TSK walked slower, had a lower cadence, took smaller steps and had an increased extension of the left knee. While previous studies [2, 3] reported a decreased range of motion in axSpa patients compared to healthy subjects our results suggest that this can not only result from disease status itself, but that gait kinematics are associated with fear of movement. This is important to consider when gait analysis is used to assess the effect of interventions on functional status in SpA patient

AB1528-HPR FULL BODY HAPTIC BODYSUIT - AN INSTRUMENT TO MEASURE THE RANGE AND SPEED OF MOTION IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS (axSpA) - PRELIMINARY RESULTS - Weber, N.; Lennartz, Rebecca; Knitza, Johannes; Bayat, Sara; Sadeghi, Misha; Ibrahim, Alzhraa; Karatastan, C.; Sudhakar, A.; Ramzezanzadegan, N.; Kahali, S.; Mirzayev, A.; Schuster, Louis; et al. (Annals of the Rheumatic Diseases, 2022)
Movement of the spine is restricted in axial spondyloarthritis (axSpA) [1]. Spine function is usually assessed by the Bath Ankylosing Spondylitis Metrology Index (BASMI), which is based on a limited set of defined motions that are measured semiquantitatively in the spatial dimension but not in the temporal dimension. Sensor-based measurement of spine function in axSpA patients is in its infancy but may provide a deeper and more detailed understanding of the impact of axSpA on the impairment of spine function [2,3]. In theory, unbiased full body assessment of spine motion may open a new dimension in function analysis in axSpA.<br

ACCURACY AND PERFORMANCE OF A HANDHELD ULTRASOUND DEVICE TO ASSESS ARTICULAR AND PERIARTICULAR PATHOLOGIES IN PATIENTS WITH INFLAMMATORY ARTHRITIS - Corte, G.; Bayat, Sara; Tascilar, Koray; Valor, L.; Schuster, Louis; Knitza, Johannes; Schett, Georg; Kleyer, Arnd; Simon, David (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

A Detailed Analysis of the Association between Urate Deposition and Erosions and Osteophytes in Gout - Pecherstorfer, Caroline; Simon, David; Unbehend, Sara; Ellmann, Hanna; Englbrecht, Matthias; Hartmann, Fabian; Figueiredo, Camille; Hueber, Axel; Haschka, Judith; Kocijan, Roland; Kleyer, Arnd; Schett, Georg; et al. (ACR Open Rheumatology, 2020)
ObjectiveTo characterize in detail the structural bone changes associated with the deposition of monosodium urate crystals in the first metatarsophalangeal (MTP1) joint in patients with tophaceous gout.
CRIS-Team WoS Importer:2021-07-16

Advanced machine learning for predicting individual risk of flares in rheumatoid arthritis patients tapering biologic drugs - Vodencarevic, Asmir; Tascilar, Koray; Reiser, Michaela; Hueber, Axel; Haschka, Judith; Bayat, Sara; Meinderink, Timo; Knitza, Johannes; Mendez, Larissa; Hagen, Melanie; Krönke, Gerhard; Rech, Jürgen; et al. (Arthritis Research & Therapy, 2021)
Background: Biological disease-modifying anti-rheumatic drugs (bDMARDs) can be tapered in some rheumatoid arthritis (RA) patients in sustained remission. The purpose of this study was to assess the feasibility of building a model to estimate the individual flare probability in RA patients tapering bDMARDs using machine learning methods. Methods: Longitudinal clinical data of RA patients on bDMARDs from a randomized controlled trial of treatment withdrawal (RETRO) were used to build a predictive model to estimate the probability of a flare. Four basic machine learning models were trained, and their predictions were additionally combined to train an ensemble learning method, a stacking meta-classifier model to predict the individual flare probability within 14 weeks after each visit. Prediction performance was estimated using nested cross-validation as the area under the receiver operating curve (AUROC). Predictor importance was estimated using the permutation importance approach. Results: Data of 135 visits from 41 patients were included. A model selection approach based on nested cross-validation was implemented to find the most suitable modeling formalism for the flare prediction task as well as the optimal model hyper-parameters. Moreover, an approach based on stacking different classifiers was successfully applied to create a powerful and flexible prediction model with the final measured AUROC of 0.81 (95%CI 0.73–0.89). The percent dose change of bDMARDs, clinical disease activity (DAS-28 ESR), disease duration, and inflammatory markers were the most important predictors of a flare. Conclusion: Machine learning methods were deemed feasible to predict flares after tapering bDMARDs in RA patients in sustained remission.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Flare prediction; Machine learning; Rheumatoid arthritis

Advanced neural networks for classification of MRI in psoriatic arthritis, seronegative, and seropositive rheumatoid arthritis - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Rheumatology, 2022)
Objectives: To evaluate whether neural networks can distinguish between seropositive rheumatoid arthritis (RA), seronegative RA and psoriatic arthritis (PsA) based on inflammatory patterns from hand MRI and to test how psoriasis patients with subclinical inflammation fit into such patterns. Methods: ResNet neural networks were utilized to compare (i) seropositive RA vs. PsA, (ii) seronegative RA vs. PsA and (iii) seropositive vs. seronegative RA with respect to hand MRI data. Results from T1 coronal, T2 coronal, T1 coronal and axial fat suppressed contrast-enhanced (CE) and T2 fat suppressed axial sequences were used. The performance of such trained networks was analyzed by the area-under-the-receiver-operating-characteristic curve (AUROC) with and without presentation of demographic and clinical parameters. Additionally, the trained networks were applied to psoriasis patients without clinical arthritis. Results: MRI scans from 649 patients (135 seronegative RA, 190 seropositive RA, 177 PsA, 147 psoriasis) were fed into ResNet neural networks. AUROC was 75% for seropositive RA vs. PsA, 74% for seronegative RA vs. PsA and 67% for seropositive vs. seronegative RA. All MRI sequences were relevant for classification, however, when deleting contrast agent-based sequences the loss of performance was only marginal. The addition of demographic and clinical data to the networks did not provide significant improvements for classification. Psoriasis patients were mostly assigned to PsA by the neural networks, suggesting that a PsA-like MRI pattern may be present early in the course of psoriatic disease. Conclusion: Neural networks can be successfully trained to distinguish MRI inflammation related to seropositive RA, seronegative RA, and PsA.
Keywords: Rheumatoid arthritis; Psoriatic arthritis; neural networks; deep learning

A LONGITUDINAL DUAL ENERGY COMPUTED TOMOGRAPHY STUDY ON THE EFFECT OF URATE LOWERING THERAPIES ON THE REDUCTION OF TOPHUS BURDEN IN PATIENTS WITH CHRONIC GOUT - Ellmann, Hanna; Bayat, Sara; D'Oliveira, I.; Englbrecht, Matthias; Araujo, E.; Mendonca, S.; Lell, Michael; Manger, Bernhard; Schett, Georg; Rech, Jürgen; Cavallaro, Alexander Josef (2016)
EVALuna2:13439

Association of Structural Entheseal Lesions With an Increased Risk of Progression From Psoriasis to Psoriatic Arthritis - Simon, David; Tascilar, Koray; Kleyer, Arnd; Bayat, Sara; Kampylafka, Eleni; Sokolova, Maria; Zekovic, Ana; Hueber, Axel; Rech, Jürgen; Schuster, Louis; Engel, Klaus; Sticherling, Michael; et al. (Arthritis and Rheumatology, 2021)
Objective. To test whether the presence of structural entheseal lesions in psoriasis patients influences the risk of progression to psoriatic arthritis (PsA).
CRIS-Team WoS Importer:2022-01-07

Baricitinib Improves Bone Biomechanical Properties in Rheumatoid Arthritis (RA) - Results of a Prospective Interventional Study - Kemenes, Stephan; Hartmann, Fabian; Tascilar, Koray; Simon, David; Bayat, Sara; Krönke, Gerhard; Mendez, Larissa Valor; Schuster, Louis; Liphardt, Anna-Maria; Schett, Georg; Kleyer, Arnd (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Baricitinib Improves Bone Properties and Biomechanics in Patients With Rheumatoid Arthritis: Results of the Prospective Interventional BARE BONE Trial - Simon, David; Minopoulou, Ioanna; Kemenes, Stephan; Bayat, Sara; Tascilar, Koray; Mutlu, Melek Yalcin; Valor-Méndez, Larissa; Krönke, Gerhard; Hueber, Axel J.; Schett, Georg; Kleyer, Arnd (Arthritis and Rheumatology, 2023)
Objective: Rheumatoid arthritis (RA) is characterized by erosive joint damage, deterioration of bone mass, and biomechanics. Preclinical evidence suggests a beneficial effect of Janus kinase inhibition (JAKi) on bone properties, but clinical data are scarce to date. In this study, we evaluated the effect of JAKi through baricitinib (BARI) on 1) volumetric bone mineral density (vBMD), bone microstructure, biomechanics, and erosion repair and 2) synovial inflammation in RA patients. Methods: Prospective, single-arm, interventional, open-label, single-center phase 4 study in RA patients with pathological bone status and clinical indication of JAKi (BARE BONE trial). Participants received BARI (4 mg/day) over 52 weeks. To assess bone properties and synovial inflammation, high-resolution computed tomography scans and magnetic resonance imaging were performed at baseline (BL), week 24, and week 52. Clinical response and safety were monitored. Results: Thirty RA patients were included. BARI significantly improved disease activity (Disease Activity Score in 28 joints using the erythrocyte sedimentation rate: 4.82 ± 0.90 to 2.71 ± 0.83) and synovial inflammation (RAMRIS synovitis score: 5.3 [4.2] to 2.7 [3.5]). We observed a significant improvement in trabecular vBMD with a mean change of 6.11 mgHA/mm3 (95% confidence interval [95% CI] 0.01–12.26). Biomechanical properties also improved with mean change from baseline in estimated stiffness of 2.28 kN/mm (95% CI 0.30–4.25) and estimated failure load of 98.8 N (95% CI 15.9–181.7). The number and size of erosions in the metacarpal joints remained stable. No new safety signals with BARI treatment were observed. Conclusion: Bones of RA patients improve with BARI therapy, as shown by an increase in trabecular bone mass and an improvement of biomechanical properties.
CRIS-Team Scopus Importer:2023-09-29

BARICITINIB LEADS TO RAPID AND PERSISTENT RESOLUTION OF SYNOVITIS AS MEASURED BY HAND MRI IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS (RA) FAILING CS/BDMARD THERAPY - Kemenes, S.; Bayat, Sara; Simon, David; Krönke, Gerhard; Bohr, D.; Valor, L.; Hartmann, F.; Schuster, Louis; Tascilar, Koray; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Biomechanical stress in the context of competitive sports training triggers enthesitis - Simon, David; Kleyer, Arnd; Bayat, Sara; Knitza, Johannes; Valor-Mendez, Larissa; Schweiger, Marina; Schett, Georg; Tascilar, Koray; Hueber, Axel (Arthritis Research & Therapy, 2021)
Objective To evaluate the influence of mechanical stress on the development of immediate enthesitis. Methods The BEAT study is an interventional study that assessed entheses in competitive badminton players before and immediately after a 60-min intensive training session. Power Doppler (PD) signal and Gray scale (GS) changes were assessed in the insertion sites of both Achilles tendon, patellar tendons, and lateral humeral epicondyles and quantified using a validated scoring system. Results Thirty-two badminton players were included. One hundred ninety-two entheseal sites were examined twice. The respective empirical total scores for PD examination were 0.1 (0.3) before and 0.5 (0.9) after training. Mean total GS scores were 2.9 (2.5) and 3.1 (2.5) before and after training, respectively. The mean total PD score difference of 0.4 between pre- and post-training was significant (p = 0.0014), whereas no significant difference for the mean total GS score was observed. Overall, seven participants (22%) showed an increased empirical total PD score. A mixed effects model showed a significant increase of PD scores after training, with a mean increase per site of 0.06 (95% CI 0.01 to 0.12, p = 0.017). Conclusions Mechanical stress leads to rapid inflammatory responses in the entheseal structures of humans. These data support the concept of mechanoinflammation in diseases associated with enthesitis.
CRIS-Team WoS Importer:2021-07-09

BIOMECHANICAL STRESS IN THE CONTEXT OF COMPETITIVE SPORTS TRAINING TRIGGERS ENTHESITIS - Simon, David; Kleyer, Arnd; Bayat, Sara; Knitza, Johannes; Valor, L.; Schweiger, M.; Schett, Georg; Tascilar, Koray; Hueber, Axel (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-09-24

Blood-Based Biomarkers of Inflammation and Tissue Remodeling Can Discriminate Between Rheumatoid Arthritis, Psoriasis, and Psoriatic Arthritis and Are Associated with Hand Function - Port Linares, Helena; Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne-Christine; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Heinrich, Simon; et al. (poster, American College of Rheumatology Convergence, 2023)

Bone Mass, Bone Microstructure and Biomechanics in Patients with Hand Osteoarthritis - Simon, David; Tascilar, Koray; Unbehend, Sara; Bayat, Sara; Berlin, Andreas; Liphardt, Anna-Maria; Meinderink, Timo; Rech, Jürgen; Hueber, Axel; Schett, Georg; Kleyer, Arnd (Journal of Bone and Mineral Research, 2020)
The impact of primary hand osteoarthritis (HOA) on bone mass, microstructure, and biomechanics in the affected skeletal regions is largely unknown. HOA patients and healthy controls (HCs) underwent high-resolution peripheral quantitative computed tomography (HR-pQCT). We measured total, trabecular, and cortical volumetric bone mineral densities (vBMDs), microstructural attributes, and performed micro–finite element analysis for bone strength. Failure load and scaled multivariate outcome matrices from distal radius and second metacarpal (MCP2) head measurements were analyzed using multiple linear regression adjusting for age, sex, and functional status and reported as adjusted Z-score differences for total and direct effects. A total of 105 subjects were included (76 HC: 46 women, 30 men; 29 HOA: 23 women, six men). After adjustment, HOA was associated with significant changes in the multivariate outcome matrix from the MCP2 head (p <.001) (explained by an increase in cortical vBMD (Δz = 1.07, p =.02) and reduction in the trabecular vBMD (Δz = −0.07, p =.09). Distal radius analysis did not show an overall effect of HOA; however, there was a gender-study group interaction (p =.044) explained by reduced trabecular vBMD in males (Δz = −1.23, p =.02). HOA was associated with lower failure load (−514 N; 95%CI, −1018 to −9; p = 0.05) apparent in males after adjustment for functional status. HOA is associated with reduced trabecular and increased cortical vBMD in the MCP2 head and a reduction in radial trabecular vBMD and bone strength in males. Further investigations of gender-specific changes of bone architecture in HOA are warranted. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.
CRIS-Team Scopus Importer:2020-06-09
Keywords: ANALYSIS/QUANTITATION OF BONE; BIOMECHANICS; BONE QCT/MICROCT; DISEASES AND DISORDERS OF/RELATED TO BONE; ORTHOPAEDICS; OSTEOARTHRITIS

Bone Microstructure Assessed By Hrpqct in Subjects with Hyperuricemia without Arthritis - Kocijan, Roland; Nia, Arastoo; Muschitz, Christian; Simon, David; Geiger, Corinna; Haschka, Judith; Kleyer, Arnd; Bayat, Sara; Rech, Jürgen; Kocijan, Annemarie; Dzirlo, Larissa; Graninger, Monika; et al. (2015)
EVALuna2:13325

CHRONIC TENOSYNOVITIS IS ASSOCIATED WITH LOSS OF GRIP STRENGTH IN PATIENTS WITH PSORIASIS AND PSORIATIC ARTHRITIS (OP0069) - Bayat, Sara; Coppers, Birte; Kleyer, Arnd; Elie-Tino, Godonou; Valor, L.; Simon, David; Fagni, Filippo; Corte, Giulia; Schönau, Verena; Tascilar, Koray; Hueber, Axel; Sticherling, Michael; et al. (Annals of the Rheumatic Diseases, 2023)
Background Rheumatic diseases result in joint destruction and impaired physical function [1]. We recently showed, that hand function based on objective tests may serve as a biomarker representing subclinical inflammation in psoriasis (Pso) patients and thus could support the early detection of psoriatic arthritis (PsA) onset [2]. Hand function tests are relevant for objective assessment of musculoskeletal function in relation to disease activity in PsA [3], However, the relationship of hand function with the synovitis and tenosynovitis detected by ultrasound (US) in PsA and Pso patients has not been well studied. Objectives To investigate the association of synovitis and tenosynovitis detected by US in greyscale (GS) and power doppler (PD) activity with grip strength and fine motor skills in patients with PsA and Pso. Methods PsA and Pso patients were recruited from the Rheumatology Department at the University Hospital erlangen, for this cross-sectional study. After giving written informed consent, subject characteristics were recorded and study participants underwent bilateral US of the wrists, metacarpophalangeal (MCP) joints, and flexor tendons of all fingers. Each joint was examined by GS (0-3), PD (0-3) and finally a combined score (PDUS: PD + GS) was calculated (0-3) [4]. The flexor tendon was scanned in GS (0/1) and with PD [0-3]. US activity considered either a synovitis or tenosynovitis score ≥1. Activity in tender joint count (TJC) and swollen joint count (SJC) 68/66 was considered ≥1 tender or ≥1 swollen joint. Hand function was assessed by vigorimetric grip strength (lbf) and the fine motor skill MPUT (Moberg pick-up test). For the analysis, patients’ hands were either divided in dominant/non-dominant or patient reported affected/non-affected hand. A correlation matrix was applied to measure the linear relation between the pairs of synovitis and tenosynovitis scores, grip strength and MPUT for both hands, using the Spearman correlation method. Results 106 patients (40 PsA, 66 Pso) participated in this study. Subject characteristics and general outcomes are summarized in Table 1. While grip strength was higher in the dominant hand (p<0.001), MPUT times are comparable between the dominant vs. non-dominant hands (p=0.056) but was faster in the non-affected hand (p=0.008). Low to moderate positive correlations were observed between both, overall GS synovitis score (MCP 2-5 + wrist) (r=0.24, p<0.05), and PDUS (r=0.23, p<0.05) with MPUT. In US active patients, a high correlation between grip strength and GS tenosynovitis score in digit 2 (r=-0.566, p=0.028) was detected. When considering patients with US in addition to SJC/TJC activity, imaging modalities did not correlate with hand function. Conclusion These findings indicate that the synovitis detected by greyscale is related with fine motor skills and tenosynovitis in greyscale with grip strength. This suggests, that chronic tenosynovitis has a greater impact on hand function than the acute inflammatory phase. When considering patients with TJC68/SJC66 ≥1 this relation is not present, suggesting that clinically assessed joint count, unlike ultrasonography, does not correlate with hand function impairmen

Cinematic Rendering Enables Depiction of Bone Anabolic Effects in Patients Treated with Baricitinib - Bayat, Sara; Simon, David; Schuster, Louis; Schett, Georg; Kleyer, Arnd (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

CLASSIFICATION OF PSORIATIC ARTHRITIS, SERONEGATIVE RHEUMATOID ARTHRITIS, AND SEROPOSITIVE RHEUMATOID ARTHRITIS USING DEEP LEARNING ON MAGNETIC RESONANCE IMAGING - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Supplement 1, 2022)
Background: While MRI evaluation of joints has been primarily used to quantify inflammation at a cross-sectional and longitudinal level, less is known about the potential of MRI in distinguishing different patterns of inflammation in the various forms of arthritis. Objectives: To evaluate (i) whether deep learning using neural networks can be trained to distinguish between seropositive rheumatoid arthritis (RA+), seronegative RA (RA-), and psoriatic arthritis (PsA) based on structural inflammatory patterns on hand magnetic resonance imaging and (ii) to assess if psoriasis patients with subclinical inflammation fit into such patterns. Methods: ResNet 3D [1] neural networks were trained to distinguish (i) RA+ vs. PsA, (ii) RA- vs. PsA and (iii) RA+ vs. RA- with respect to hand MRI data. Diagnosis of patients was determined using the following guidelines: ACR/EULAR 2010 [2] for RA and CASPAR [3] for PsA. Results from T1 coronal, T2 coronal, T1 coronal and axial fat suppressed contrast-enhanced (CE) and T2 fat suppressed axial sequences were used. The performance of such trained networks was analyzed by the area-under-the-receiver-operating-characteristic curve (AUROC) with and without imputation of demographic and clinical parameters ( Figure 1A ). Additionally, the trained networks were applied to psoriasis patients without clinical signs of PsA. Results: MRI scans from 649 patients (135 RA-, 190 RA+, 177 PsA, 147 psoriasis) were included ( Table 1 ). The AUROC for differentiation between disease entities was 75% (SD 3%) for RA+ vs. PsA, 74% (SD 8%) for RA- vs. PsA, and 67% (6%) for RA+ vs. RA-. All MRI sequences were relevant for classification, however, when deleting CE sequences, the loss of performance was only marginal. The addition of patient-specific data to the networks did not provide significant improvements. Increasing amounts of training data demonstrated improved performance of the networks ( Figure 1B ). Psoriasis patients were mostly assigned to PsA by the neural networks, suggesting that PsA-like MRI pattern may be present early in the course of psoriatic disease. Conclusion: Deep learning can be successfully applied to differentiate MRI inflammatory patterns related to RA+, RA-, and PsA. Early changes in psoriasis patients can be recognized by neural networks and are characterized by a pattern that allowed the networks to classify them as PsA. <
Keywords: Rheumatoid arthritis; deep learning; neural networks

Deep learning-based classification of erosion, synovitis and osteitis in hand MRI of patients with inflammatory arthritis - Schlereth, Maja; Yalcin-Mutlu, Melek; Utz, Jonas; Bayat, Sara; Heimann, Tobias; Qiu, Jingna; Ehring, Chris; Liu, Chang; Uder, Michael; Kleyer, Arnd; Simon, David; Roemer, Frank; et al. (RMD Open, 2024)
OBJECTIVES: To train, test and validate the performance of a convolutional neural network (CNN)-based approach for the automated assessment of bone erosions, osteitis and synovitis in hand MRI of patients with inflammatory arthritis. METHODS: Hand MRIs (coronal T1-weighted, T2-weighted fat-suppressed, T1-weighted fat-suppressed contrast-enhanced) of rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients from the rheumatology department of the Erlangen University Hospital were assessed by two expert rheumatologists using the Outcome Measures in Rheumatology-validated RA MRI Scoring System and PsA MRI Scoring System scores and were used to train, validate and test CNNs to automatically score erosions, osteitis and synovitis. Scoring performance was compared with human annotations in terms of macro-area under the receiver operating characteristic curve (AUC) and balanced accuracy using fivefold cross-validation. Validation was performed on an independent dataset of MRIs from a second patient cohort. RESULTS: In total, 211 MRIs from 112 patients (14 906 region of interests (ROIs)) were included for training/internal validation using cross-validation and 220 MRIs from 75 patients (11 040 ROIs) for external validation of the networks. The networks achieved high mean (SD) macro-AUC of 92%±1% for erosions, 91%±2% for osteitis and 85%±2% for synovitis. Compared with human annotation, CNNs achieved a high mean Spearman correlation for erosions (90±2%), osteitis (78±8%) and synovitis (69±7%), which remained consistent in the validation dataset. CONCLUSIONS: We developed a CNN-based automated scoring system that allowed a rapid grading of erosions, osteitis and synovitis with good diagnostic accuracy and using less MRI sequences compared with conventional scoring. This CNN-based approach may help develop standardised cost-efficient and time-efficient assessments of hand MRIs for patients with arthritis.
CRIS-Team Scopus Importer:2024-06-28
Keywords: classification; machine learning; magnetic resonance imaging; psoriatic arthritis; rheumatoid arthritis

Does Subjectively Perceived Loss Of Hand Function Sufficiently Represent Ultrasonography-Detected Synovitis And Tenosynovitis In Patients With Psoriasis And Psoriatic Arthritis? - Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Valor-Mendez, Larissa; Fagni, Filippo; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Schett, Georg; Kleyer, Arnd; et al. (poster, European Alliance of Association for Rheumatology (EULAR) Congress, 2023)

Effect of disease-modifying anti-rheumatic drugs on bone structure and strength in psoriatic arthritis patients - Simon, David; Kleyer, Arnd; Bayat, Sara; Tascilar, Koray; Kampylafka, Eleni; Meinderink, Timo; Schuster, Louis; Petrov, Ramona; Liphardt, Anna-Maria; Rech, Jürgen; Schett, Georg; Hueber, Axel (Arthritis Research & Therapy, 2019)
Objectives: To address whether the use of methotrexate (MTX) and biological disease-modifying anti-rheumatic drugs (bDMARDs) impacts bone structure and biomechanical properties in patients with psoriatic arthritis (PsA). Methods: This is a cross-sectional study in PsA patients receiving no DMARDs, MTX, or bDMARDs. Volumetric bone mineral densities (vBMDs), microstructural parameters, and biomechanical properties (stiffness/failure load) were determined by high-resolution peripheral quantitative CT and micro-finite element analysis in the respective groups. Bone parameters were compared between PsA patients with no DMARDs and those receiving any DMARDs, MTX, or bDMARDs, respectively. Results: One hundred sixty-five PsA patients were analyzed, 79 received no DMARDs, 86 received DMARDs, of them 52 bDMARDs (TNF, IL-17-or IL-12/23 inhibitors) and 34 MTX. Groups were balanced for age, sex, comorbidities, functional index, and bone-active therapy, while disease duration was longest in the bDMARD group (7.8 ± 7.4 years), followed by the MTX group (4.6 ± 7.4) and the no-DMARD group (2.9 ± 5.2). No difference in bone parameters was found between the no-DMARD group and the MTX group. In contrast, the bDMARD group revealed significantly higher total (p = 0.001) and trabecular vBMD (p = 0.005) as well as failure load (p = 0.012) and stiffness (p = 0.012). In regression models, age and bDMARDs influenced total vBMD, while age, sex, and bDMARDs influenced failure load and stiffness. Conclusion: Despite longer disease duration, bDMARD-treated PsA patients benefit from higher bone mass and better bone strength than PsA patients receiving MTX or no DMARDs. These data support the concept of better control of PsA-related bone disease by bDMARDs.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Biological agents; Bone; Computed tomography; Disease-modifying anti-rheumatic drugs; Methotrexate; Psoriatic arthritis

Effects of Conventional Uric Acid-Lowering Therapy on Monosodium Urate Crystal Deposits - Ellmann, Hanna; Bayat, Sara; Guilhon de Araujo, Elizabeth; Manger, Bernhard; Kleyer, Arnd; Cavallaro, Alexander; Lell, Michael; Schenker, Hannah; Simon, David; Tascilar, Koray; Baraf, Herbert S. B.; Schett, Georg; et al. (Arthritis and Rheumatology, 2019)
Objective Few studies have systematically and quantitatively addressed the impact of urate-lowering therapy on monosodium urate (MSU) deposits. This study was undertaken to analyze the effect of lifestyle measures and conventional urate-lowering therapy on MSU deposits in patients with gout. Methods In this prospective study, subjects with gout according to the American College of Rheumatology/European League Against Rheumatism classification criteria and presence of MSU deposits seen on dual-energy computed tomography (DECT) scans received either lifestyle intervention or conventional urate-lowering therapy for a mean period of 18 months before a follow-up DECT scan. Detected MSU deposits were quantified by volumetric measurement and validated by semiquantitative scoring, and baseline and follow-up measurements were compared. Results Baseline and follow-up DECT scans were available for all 83 subjects. Six subjects discontinued treatment, and 77 subjects underwent a lifestyle intervention (n = 24) or were treated with allopurinol (n = 29), febuxostat (n = 22), or benzbromarone (n = 2) over the entire observation period. The mean serum uric acid (UA) level decreased from 7.2 to 5.8 mg/dl in the overall population. In patients who discontinued treatment, no change in MSU deposits or serum UA levels was observed. The burden of MSU deposits significantly decreased in patients undergoing lifestyle intervention (MSU volume P = 0.007; MSU score P = 0.001), and in patients treated with allopurinol (MSU volume and score P < 0.001) or febuxostat (MSU volume P < 0.001; MSU score P = 0.001). No significant decline in MSU deposits was noted in patients who discontinued treatment. Conclusion These data show that lifestyle intervention and xanthine oxidase inhibitors significantly decrease the MSU deposit burden. Hence, conventional gout therapy not only lowers serum UA levels, but also reduces pathologic MSU deposits.
CRIS-Team WoS Importer:2019-12-20

Effects of ustekinumab versus tumor necrosis factor inhibition on enthesitis: Results from the enthesial clearance in psoriatic arthritis (ECLIPSA) study - Guilhon de Araujo, Elizabeth; Englbrecht, Matthias; Höpken, Sabrina; Finzel, Stephanie; Kampylafka, Eleni; Kleyer, Arnd; Bayat, Sara; Schoenau, Verena; Hueber, Axel; Rech, Jürgen; Schett, Georg (Seminars in Arthritis and Rheumatism, 2018)
OBJECTIVES: To date, all studies addressing on anti-inflammatory drugs in PsA have been carried out in psoriatic arthritis (PsA) patients with polyarticular disease. Specific studies on enthesitis are missing. IL-23 is considered to play a central role in the development of enthesitis. We therefore speculated that therapeutic inhibition of IL-12/IL-23 is particularly effective in enthesitis-driven PsA patients. METHODS: Enthesial CLearance In PSoriatic Arthritis (ECLIPSA) is a prospective randomized-controlled open-label study. Patients with PsA with active enthesitis were randomized 1:1 to receive either ustekinumab (UST; arm 1) or tumor necrosis factor inhibitors (TNFi; arm 2). Primary endpoint was complete clearance of enthesitis, defined by Spondyloarthritis Research Consortium of Canada (SPARCC) index equal to zero at 24weeks. RESULTS: 51 patients (UST = 25; TNFi = 26) were screened, 47 enrolled (UST = 23; TNFi = 24) and 46 completed the study. Mean ± SD SPARCC index at baseline was 4.8 ± 2.6 in the UST group and 3.5 ± 2.3 in the TNFi group with no significant difference. After 24 weeks, 73.9% of UST patients and 41.7% of TNFi patients reached the primary endpoint (SPARCC = 0) indicating clearance from enthesitis (p = 0.018). UST achieved superior responses as compared to TNFi with respect to enthesitis (p = 0.007) and psoriatic skin disease (p = 0.030) but not for arthritis (p = 0.95). CONCLUSION: These results indicate that p40-IL-12/IL-23 inhibition is superior to TNFi in the clearance of enthesitis. Future stratified therapeutic approaches in PsA patients may therefore consider the presence or absence of enthesitis as a discriminator of response between different cytokine blocking modalities.
EVALuna2:34482

Efficacy and drug persistence of baricitinib monotherapy is similar to combination therapy in patients with active RA: a prospective observational study - Bayat, Sara; Tascilar, Koray; Bohr, Daniela; Krönke, Gerhard; Simon, David; Knitza, Johannes; Hartmann, Fabian; Schett, Georg; Kleyer, Arnd (RMD Open, 2022)
BACKGROUND: Baricitinib (BARI) is approved for the treatment of rheumatoid arthritis (RA) after failure of conventional synthetic and biologic disease modifying anti-rheumatic drugs (cs/bDMARDs) in combination with methotrexate (MTX) or as monotherapy. However, real-world data are scarce regarding efficacy and drug persistence for BARI monotherapy (BARI-mono) versus its combination with MTX (BARI-combo). OBJECTIVE: To evaluate efficacy and drug persistence of BARImono compared with BARI-combo in routine clinical practice METHODS: Patients with RA who were switched to BARI were included in a prospective, monocentric cohort. Demographics, clinical outcomes, adverse events and medication were prospectively recorded every 3 months. Clinical efficacy was measured by DAS-28 ESR while drug persistence was measured as the time on drug. We estimated least-square mean DAS-28 scores over time using linear mixed effects models including time-group interactions. Kaplan-Meier method was used to estimate BARI survival and probability of remission over time. RESULTS: 139 patients (98 women; aged 58.4 (12.8) years; mean disease duration of 9.7 years) were included between 2017 and 2021. 46 patients received BARI-combo, 93 patients received BARI-mono. Mean DAS-28 ESR were not significantly but only numerically different between both groups at baseline and multiple timepoints over follow-up. DAS-28 ESR remission was attained at least once upto 48 weeks in 62% and 51% patients in BARI-combo versus BARI-mono group (log-rank p=0.64). Drug persistence was high (69 vs 67% at 48 weeks and 62% vs 56% at 96 weeks) and similar in BARI-combo-treated and BARI-mono-treated patients. b/ts DMARD naïve patients had lower mean DAS-28 scores over the follow-up and attained DAS-28 ESR remission earlier than patients with inadequate response to b/ts DMARDs (p=0.11). BARI was discontinued in 11/139 patients (7.9%) due to adverse effects. CONCLUSION: In routine practice, BARI is effective as monotherapy in case of MTX intolerance with overall high drug persistence rates. No new safety signals were observed.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Baricitinib; Combination treatment; Drug survival; Remission; Rheumatoid Arthritis

Establishment and evaluation of a sensor-based method to assess hand function in patients with rheumatoid arthritis - Coppers, Birte; Phutane, Uday; Berisha, Dardan; Tascilar, Koray; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Heinrich, Simon; Bayat, Sara; et al. (conference, World Biomechanics Congress 2022, 2022)

Evaluation of marker-based motion capturing to charactherize basic hand movements in rheumatic patients - Coppers, Birte; Heinrich, Simon; Phutane, Uday; Berisha, Dardan; Tascilar, Koray; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Bayat, Sara; et al. (27th Congress of the European Society of Biomechanics, 2022)

Feasibility of using optoelectronic measurement of hand movement for characterizing hand function in rheumatoid arthritis - Coppers, Birte; Heinrich, Simon; Phutane, Uday; Berisha, Dardan; Tascilar, Koray; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Johanna; Bayat, Sara; et al. (75th EULAR (European Alliance of Associations for Rheumatology), European Congress of Rheumatology 2022, 2022)

Fibroblast Activation in Psoriasis Patients Assessed by Ga-68-FAPI-04 PET-CT Is Associated with Progression to Psoriatic Arthritis - Fagni, Filippo; Simon, David; Kleyer, Arnd; Tascilar, Koray; Taubmann, Jule; Bayat, Sara; Minopoulou, Ioanna; Mutlu, Melek Yalcin; Atzinger, Armin; Kuwert, Torsten; Schett, Georg; Schmidkonz, Christian (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

FINE STRUCTURE ANALYSIS OF THE INTER-RELATION BETWEEN TOPHUS DEPOSITION AND BONE LESIONS IN GOUT USING A COMBINATION OF DUAL ENERGY AND HIGH-RESOLUTION CT - Bayat, Sara; Simon, David; Pecherstorfer, Caroline; Ellmann, Hanna; Figueiredo, C.; Englbrecht, Matthias; Hueber, A.; Kleyer, Arnd; Rech, Jürgen; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

High Impact Sports Leads to Inflammatory Responses at Entheseal Sites Results of the BEAT Study (Badminton Enthesitis Arthrosonography Study) - Simon, David; Kleyer, Arnd; Tascilar, Koray; Bayat, Sara; Knitza, Johannes; Valor-Mendez, Larissa; Schweiger, Marina; Schett, Georg; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

HIGH REMISSION RATES IN RA - REAL LIFE DATA FROM BARITICINIB - Bayat, Sara; Tascilar, K.; Kaufmann, V.; Kleyer, Arnd; Simon, David; Knitza, Johannes; Hartmann, F.; Adam, Susanne; Hueber, A.; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Identification of circulating microRNA patterns in patients in psoriasis and psoriatic arthritis - Haschka, Judith; Simon, David; Bayat, Sara; Messner, Zora; Kampylafka, Eleni; Fagni, Filippo; Skalicky, Susanna; Hackl, Matthias; Resch, Heinrich; Zwerina, Jochen; Kleyer, Arnd; Cavallaro, Alexander Josef; et al. (Rheumatology, 2023)
Objective miRNAs are small non-coding RNAs that control gene expression. Specific intra- and extracellular miRNA signatures have been identified in various diseases. Whether certain miRNA signatures are associated with psoriasis (PsO) and PsA is currently unknown. We aimed to search for circulating miRNA signatures associated with PsO and PsA patients. Methods Expression of miRNAs was analysed by reverse transcription quantitative real-time PCR (RT-qPCR) in the serum of PsA, PsO patients and healthy controls. Demographic and disease-specific characteristics and imaging data from hand MRI were recorded. In the discovery phase, 192 miRNA assays were analysed in 48 samples (PsA, PsO, controls: each N = 16). For validation, 17 selected miRNAs were measured in the total population. Results A total of 141 patients and controls were analysed (51 PsA, 40 PsO, 50 controls). In the discovery phase 51 miRNAs in PsO and 64 miRNAs in PsA were down- or upregulated compared with controls, with 33 miRNAs being changed in both (adj. P < 0.05). The 17 top candidates from discovery were assessed in the validation phase, 9 of them discriminated PsA and PsO from controls [area under the curve (AUC) >= 0.70, all P < 0.05]. Four miRNAs (miR-19b-3p, miR-21-5p, miR-92a-3p and let-7b-5p) were significantly differently regulated between PsO and PsA. A combination of these miRNAs increased the AUC to 0.92 in multivariate regression model to discriminate PsO and PsA. Conclusion miRNA signatures in PsA and PsO patients differ from controls. Nine miRNAs were differentially regulated in PsA and PsO patients, five of them previously reported to be involved in bone and cartilage metabolism, indicating an intimate association of psoriatic inflammation and bone/cartilage changes.
CRIS-Team WoS Importer:2023-03-17

Identification of Circulating MicroRNA Signatures in Patients with Psoriasis and Psoriatic Arthritis to Develop Novel Strategies for Early Diagnosis of a Bone and Joint Involvement - Haschka, Judith; Simon, David; Bayat, Sara; Kleyer, Arnd; Kampylafka, Eleni; Muschitz, Christian; Skalicky, Susanna; Hackl, Matthias; Resch, Heinrich; Schett, Georg; Kocijan, Roland; Rech, Jürgen; et al. (ARTHRITIS & RHEUMATOLOGY, 2019)
CRIS-Team WoS Importer:2020-02-07

IDENTIFICATION OF CIRCULATING MICRORNA SIGNATURES IN PATIENTS WITH PSORIASIS WITH SUBCLINICAL JOINT DISEASE AND PATIENTS WITH PSORIATIC ARTHRITIS - Haschka, J.; Simon, David; Bayat, Sara; Messner, Z.; Kampylafka, E.; Fagni, Filippo; Skalicky, S.; Hackl, M.; Resch, H.; Zwerina, J.; Kleyer, Arnd; Sticherling, Michael; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

IMPACT OF PRIMARY HAND OSTEOARTHRITIS ON MICROSTRUCTURE AND BIOMECHANICS IN FINGER JOINTS - Simon, David; Tascilar, Koray; Unbehend, Sara; Bayat, Sara; Meinderink, Timo; Berlin, Andreas; Rech, Jürgen; Hueber, Axel; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-16

Mobile Health Usage, Preferences, Barriers, and eHealth Literacy in Rheumatology: Patient Survey Study - Knitza, Johannes; Simon, David; Lambrecht, Antonia; Raab, Christina; Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Bayat, Sara; Derungs, Adrian; Amft, Oliver; Schett, Georg; Hueber, Axel (JMIR mHealth and uHealth, 2020)
BACKGROUND: Mobile health (mHealth) defines the support and practice of health care using mobile devices and promises to improve the current treatment situation of patients with chronic diseases. Little is known about mHealth usage and digital preferences of patients with chronic rheumatic diseases. OBJECTIVE: The aim of the study was to explore mHealth usage, preferences, barriers, and eHealth literacy reported by German patients with rheumatic diseases. METHODS: Between December 2018 and January 2019, patients (recruited consecutively) with rheumatoid arthritis, psoriatic arthritis, and axial spondyloarthritis were asked to complete a paper-based survey. The survey included questions on sociodemographics, health characteristics, mHealth usage, eHealth literacy using eHealth Literacy Scale (eHEALS), and communication and information preferences. RESULTS: Of the patients (N=193) who completed the survey, 176 patients (91.2%) regularly used a smartphone, and 89 patients (46.1%) regularly used social media. Patients (132/193, 68.4%) believed that using medical apps could be beneficial for their own health. Out of 193 patients, only 8 (4.1%) were currently using medical apps, and only 22 patients (11.4%) stated that they knew useful rheumatology websites/mobile apps. Nearly all patients (188/193, 97.4%) would agree to share their mobile app data for research purposes. Out of 193 patients, 129 (66.8%) would regularly enter data using an app, and 146 patients (75.6%) would welcome official mobile app recommendations from the national rheumatology society. The preferred duration for data entry was not more than 15 minutes (110/193, 57.0%), and the preferred frequency was weekly (59/193, 30.6%). Medication information was the most desired app feature (150/193, 77.7%). Internet was the most frequently utilized source of information (144/193, 74.6%). The mean eHealth literacy was low (26.3/40) and was positively correlated with younger age, app use, belief in benefit of using medical apps, and current internet use to obtain health information. CONCLUSIONS: Patients with rheumatic diseases are very eager to use mHealth technologies to better understand their chronic diseases. This open-mindedness is counterbalanced by low mHealth usage and competency. Personalized mHealth solutions and clear implementation recommendations are needed to realize the full potential of mHealth in rheumatology.
CRIS-Team Scopus Importer:2020-08-28
Keywords: eHEALS; eHealth; mHealth; mobile applications; rheumatology; telemedicine

Neural Networks for Distinguishing Rheumatoid Arthritis from Psoriatic Arthritis by Using Magnetic Resonance Imaging - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Arthritis Rheumatol., 2022)

NON-INVASIVE IN VIVO METABOLIC PROFILING OF INFLAMMATION IN JOINTS AND ENTHESES BY OPTOACOUSTIC IMAGING - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, F.; Krönke, Gerhard; Bohr, D.; Ramming, Andreas; Hartmann, F.; Klett, Daniel; Federle, Anna; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Non-invasive metabolic profiling of inflammation in joints and entheses by multispectral optoacoustic tomography - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, Florian; Krönke, Gerhard; Bohr, Daniela; Ramming, Andreas; Hartmann, Fabian; Klett, Daniel; Federle, Anna; et al. (Rheumatology, 2022)
Objective To explore the metabolic characteristics of arthritis and enthesitis using multispectral opto-acoustic tomography (MSOT), a technology using near-infrared multispectral laser to stimulate tissues and detect the emitted acoustic energy, enabling non-invasive quantification of tissue components in vivo based on differential absorbance at multiple wavelengths. Methods We performed a cross-sectional study in patients with RA or PsA and healthy controls (HCs). Participants underwent clinical, ultrasonographic and MSOT examination of MCP and wrist joints as well as the entheses of the common extensor tendon at the lateral humeral epicondyles and of the patellar, quadriceps and Achilles tendon. MSOT-measured haemoglobin (Hb), oxygen saturation, collagen and lipid levels were quantified and scaled mean differences between affected and unaffected joints and entheses were calculated as defined by clinical examination or ultrasonography using linear mixed effects models. Results We obtained 1535 MSOT and 982 ultrasonography scans from 87 participants (34 PsA, 17 RA, 36 HCs). Entheseal tenderness was not associated with significant metabolic changes, whereas enthesitis-related sonographic changes were associated with increased total Hb, oxygen saturation and collagen content. In contrast, the presence of arthritis-related clinical and sonographic findings showed increased Hb levels, reduced oxygen saturation and reduced collagen content. Synovial hypertrophy was associated with increased lipid content in the joints. Conclusion MSOT allows determination of distinct metabolic differences between arthritis and enthesitis in a non-invasive setting in humans in vivo.
CRIS-Team WoS Importer:2022-07-22

Objective and subjective hand function reflect grade of tenosynovitis in patients with psoriasis and psoriatic arthritis - Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Valor-Mendez, Larissa; Simon, David; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Bohr, Daniela; Schönau, Verena; Sticherling, Michael; Schett, Georg; et al. (poster, Deutsche Gesellschaft für Rheumatologie Kongress, 2023)

Performance of a handheld ultrasound device to assess articular and periarticular pathologies in patients with inflammatory arthritis - Corte, Giulia; Bayat, Sara; Tascilar, Koray; Valor-Mendez, Larissa; Schuster, Louis; Knitza, Johannes; Fagni, Filippo; Schett, Georg; Kleyer, Arnd; Simon, David (Diagnostics, 2021)
The purpose of this study was to assess the accuracy and performance of a new handheld ultrasound (HHUS) machine in comparison to a conventional cart-based sonographic machine in patients with inflammatory arthritis (IA). IA patients with at least one tender and swollen joint count were enrolled. US was performed on the clinically affected joints using a cart-based sonographic device (Samsung HS40) and a HHUS device (Butterfly iQ). One blinded reader scored all images for the presence of erosions, bony enlargement, synovial hypertrophy, joint effusion, bursitis, tenosynovitis, and enthesitis. Synovitis was graded (B mode and power Doppler (PD)) by the 4-level EULAR-OMERACT scale. To avoid bias by the blinded reader, we included 67 joints of two healthy volunteers in the evaluation. We calculated the overall concordance and the concordance by type of joint and pathological finding. We also measured the time required for the US examination per joint with both devices. Thirty-two patients (20 with RA, 10 with PsA, and one each with gout and SLE-associated arthritis) were included, and 186 joints were examined. The overall raw concordance in B mode was 97% (κappa 0.90, 95% CI (0.89, 0.94)). In B mode, no significant differences were found in relation to type of joint or pathological finding examined. The PD mode of the HHUS device did not detect any PD signal, whereas the cart-based device detected a PD signal in 61 joints (33%). The portable device did not offer any time savings compared to the cart-based device (47.0 versus 46.3 s). The HHUS device was accurate in the assessment of structural damage and inflammation in patients with IA, but only in the B mode. Significant improvements are still needed for HHUS to reliably demonstrate blood flow detection in PD mode.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Handheld ultrasound device; Inflammatory arthritis; Medical ultrasound; Musculoskeletal ultrasound

PREDICTION OF FLARES FOR RHEUMATOID ARTHRITIS PATIENTS ON BIOLOGIC DMARDS USING MACHINE LEARNING AND SUBSETS OF VARIABLES AVAILABLE TO PHYSICIANS, PATIENTS AND PAYERS - Vodencarevic, A.; Tascilar, K.; Hartmann, F.; Reiser, M.; Bayat, Sara; Knitza, Johannes; Valor, L.; Hagen, Melanie; Hueber, Axel; Kleyer, Arnd; Zimmermann-Rittereiser, M.; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

Quality of a Supporting Mobile App for Rheumatic Patients: Patient-Based Assessment Using the User Version of the Mobile Application Scale (uMARS) - Lambrecht, Antonia; Vuillerme, Nicolas; Raab, Christina; Simon, David; Messner, Eva-Maria; Hagen, Melanie; Bayat, Sara; Kleyer, Arnd; Aubourg, Timothee; Schett, Georg; Hueber, Axel; Knitza, Johannes (Frontiers in Medicine, 2021)
Introduction: Mobile applications promise to improve current health care. However, current mobile app quality ratings are mostly physician-based. The aim of this study was (1) to assess the quality of the self-management app Rheuma Auszeit using the validated uMARS (User Version of the Mobile App Rating Scale) app quality assessment tool and (2) to evaluate the association between uMARS scores and patients' characteristics.
CRIS-Team WoS Importer:2021-08-20

QUANTIFICATION AND IMPACT OF SECONDARY OSTEOARTHRITIS USING HR-PQCT IN ANTI-CITRULLINATED PROTEIN ANTIBODY RHEUMATOID ARTHRITIS PATIENTS - Figueiredo, C.; Simon, David; Englbrecht, Matthias; Haschka, J.; Kleyer, Arnd; Bayat, Sara; Hueber, Axel; Pereira, R. M.; Rech, Jürgen; Schett, Georg (2017)
EVALuna2:13465

Sensor-assessed grasping time as a biomarker of functional impairment in rheumatoid arthritis - Coppers, Birte; Heinrich, Simon; Tascilar, Koray; Phutane, Uday; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Bayat, Sara; Schett, Georg; et al. (Scientific Reports, 2025)
Quantifying physical impairment in rheumatoid arthritis (RA) is important to determine disease burden and disability. Therefore, we aimed to define hand function impairments in RA patients using an opto-electronic measurement system (OMS). In this cross-sectional pilot study, spatio-temporal and hand segment data were collected during the fine motor skill Moberg Picking-Up Test (MPUT) and two elementary hand movement tasks in RA patients and healthy controls (HC) using a marker-based OMS. The duration of two MPUT movement phases (grasping, transporting 12 objects) and kinematic characteristics during the elementary movements were evaluated. We analyzed between-group differences using linear mixed-effects models accounting for within-participant clustering of hands and adjusting for age and sex. Measurements were obtained from 24 RA and 23 HC. The mean duration of the grasping phase of MPUT was longer in RA patients compared to HC while transporting times were identical, showing a significant group-phase interaction (p < 0.001). Interphalangeal joint angle ratios were similar in RA and HC (p > 0.05) with a lower ratio in both groups for the task thumb-finger opposition compared to flexion of joints. In RA patients especially grasping objects was impaired, and performance time for a subset of objects may serve as a quantitative biomarker of functional impairment.<br
CRIS-Team Scopus Importer:2025-03-14
Keywords: Biomarkers; Biomechanics; Fine-motor skills; Hand; Rheumatoid arthritis

Serum extracellular matrix biomarkers in rheumatoid arthritis, psoriatic arthritis and psoriasis and their association with hand function - Port, Helena; Coppers, Birte; Tragl, Sonja; Manger, Eva; Niemiec, Lisa Maria; Bayat, Sara; Simon, David; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne Christine; Tascilar, Koray; Hueber, Axel; et al. (Scientific Reports, 2025)
Inflammatory arthritis, including rheumatoid arthritis and psoriatic arthritis, is characterized by physical function impairment. This becomes apparent even before arthritis onset, as in psoriasis (PsO). Chronic inflammation triggers an accelerated remodeling of the extracellular matrix (ECM), resulting in released ECM fragments detectable in blood. We aimed to investigate levels of blood-based ECM biomarkers in patients with RA, PsA, PsO, and healthy controls and to explore the association of ECM biomarkers with hand function impairments. Patients with RA (n = 85), PsA (n = 115), PsO (n = 102) and controls (n = 110) were included in this cross-sectional study. ECM catabolic (C1M, C2M, C3M, C4M, PRO-C4, C6M, ARG), formation (PRO-C1, PRO-C3, PRO-C6) and inflammation biomarkers (VICM) were measured in serum from all patients. Objective hand function (fine motor skills (Moberg-Picking-Up Test), isometric grip strength (dynamometer) and patient-perceived hand function (Michigan Hand Questionnaire (MHQ)) were assessed. Patients with RA and PsA received treatment with disease-modifying anti-rheumatic drugs. VICM levels were higher in RA, PsA, and PsO than in controls (p < 0.0001). PsA and PsO showed higher C4M levels compared to controls (p < 0.0001, p < 0.0001), while C6M was lower in patients with RA, PsA and PsO than in controls (p < 0.0001, p < 0.001, p < 0.01). PsO presented with higher levels of C1M compared to controls and to RA (p < 0.001 and p < 0.0001). PRO-C6 correlated negatively with MHQ (ρ = -0.39, p < 0.01) and grip strength (ρ = -0.31, p < 0.05) in PsO, while only weak correlations were observed between biomarkers and hand function scores for RA and PsA patients (all ρ < ± 0.2–0.3). Patients with RA, PsA, and PsO showed significant alterations in ECM remodeling biomarkers. Especially PsA and PsO had higher levels of inflammatory biomarkers compared to RA and controls, likely due to modulation by treatment. Predominantly in PsO, ECM formation biomarkers were associated with hand function impairments.<br
Keywords: Extracellular matrix; Biochemical markers; Rheumatoid arthritis; Psoriatic arthritis; Psoriasis; Hand function

SIMILAR EFFICACY AND DRUG SURVIVAL RATES OF BARICITINIB MONOTHERAPY AND BARICITINIB/METHOTREXATE COMBINATION THERAPY IN REAL-LIFE TREATMENT OF RHEUMATOID ARTHRITIS - RESULTS FROM A PROSPECTIVE COHORT OF BARICITINIB-TREATED PATIENTS - Bayat, Sara; Tascilar, Koray; Bohr, D.; Simon, David; Kronke, G.; Hartmann, F.; Knitza, Johannes; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

SIZE MATTERS - EXTENT OF MONOSODIUM URATE DEPOSITS BUT NOT SERUM URATE LEVEL PREDICTS COMPLETE RESOLUTION OF MONOSODIUM URATE CRYSTAL DEPOSITS IN PATIENTS WITH GOUT - Bayat, Sara; Ellmann, Hanna; Guilhon de Araujo, Elizabeth; Manger, Bernhard; Hagen, Melanie; Kleyer, Arnd; Lell, Michael; Schenker, Hannah; Simon, David; Tascilar, Koray; Baraf, Herbert S. B.; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

SPATIOTEMPORAL DYNAMICS OF BONE LOSS BEFORE AND AFTER THE ONSET OF RHEUMATOID ARTHRITIS - Tascilar, Koray; Simon, David; Liphardt, Anna-Maria; Meinderink, Timo; Bayat, Sara; Rech, Jürgen; Hueber, A.; Krönke, Gerhard; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

STRUCTURAL ENTHESEAL LESIONS IN PSORIASIS PATIENTS ARE ASSOCIATED WITH AN INCREASED RISK OF PROGRESSION TO PSORIATIC ARTHRITIS - A PROSPECTIVE COHORT STUDY - Simon, David; Tascilar, K.; Kleyer, Arnd; Bayat, Sara; Kampylafka, E.; Hueber, Axel; Rech, Jürgen; Schuster, Louis; Engel, K.; Sticherling, Michael; Schett, Georg (ANNALS OF THE RHEUMATIC DISEASES, 2020)
CRIS-Team WoS Importer:2020-08-21

SUBJECTIVE ASSESSMENT OF PHYSICAL FUNCTION DOES NOT SUFFICIENTLY EXPLAIN VARIANCE OF MEASURED HAND FUNCTION AND GRIP STRENGTH IN ARTHRITIS PATIENTS AND NON-ARTHRITIS CONTROLS - Liphardt, Anna-Maria; Tascilar, Koray; Coppers, Birte; Manger, Eva; Liehr, Sonja; Bieniek, Lisa Maria; Bayat, Sara; Simon, David; Sticherling, Michael; Rech, Jürgen; Hueber, A.; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

The ageing joint-standard age- and sex-related values of bone erosions and osteophytes in the hand joints of healthy individuals - Berlin, Andreas; Simon, David; Tascilar, K.; Figueiredo, C.; Bayat, Sara; Finzel, Stephanie; Klaus, E.; Rech, Jürgen; Hueber, Axel; Kleyer, Arnd; Schett, Georg (Osteoarthritis and Cartilage, 2019)
Objective: To analyze the age-related changes of the physiological hand joint architecture. Method: To address this concept, healthy individuals (each 10 women and 10 men in six different age decades spanning from 21 to 80 years) were recruited through a field campaign, investigated for the absence of rheumatic diseases and other comorbidities and received high-resolution quantitative computed tomography (HR-pQCT) examination of the hand joints. Number and extent of erosions and osteophytes were quantified across the ages and different sexes. Results: Bone erosions [median (Q1–Q3), 1 (0–2)] and osteophytes [2 (1–4)] were found in healthy women and men with no significant sex differences. Structural changes however accumulated with age: the overall incidence rate ratio (IRR) for the number of erosions and osteophytes per age were 1.04 (95% CI: erosions 1.03–1.06; osteophytes: 1.03–1.05). This means a 4% increase in the number of erosions and osteophytes per year. Using third decade as reference, healthy individuals in the age decades from 50 years had higher IRR for erosion numbers (sixth, seventh, eigth decade: 4.87 (2.20–11.75), 6.81 (3.08–16.46) and 6.92 (3.11–16.79)) compared to younger subjects (fourth, fifth decade: 1.80 (0.69–4.87), 1.53 (0.59–4.10)). The IRRs of osteophytes also indicate a gradual increase after the fifth decade, with IRRs of 2.32 (1.32–4.17), 4.17 (2.38–7.49) and 6.86 (3.97–12.20) for the sixth, seventh and eigth decades, respectively. Conclusions: Structural changes in the hand joints of healthy individuals are age dependent. While being rare under 50 years of age, erosions and osteophytes accumulate above the age of 50, suggesting that the threshold between “normal” and “pathological” is shifted with the increase of age.
CRIS-Team Scopus Importer:2019-06-07
Keywords: Bone erosions; Computed tomography; Hand joints; Healthy individuals; Osteophytes

The Influence of Hand Osteoarthritis on Bone Microstructure and Biomechanical Properties of Radial Bone - Simon, David; Unbehend, Sara; Bayat, Sara; Rech, Jürgen; Hueber, Axel; Schett, Georg; Kleyer, Arnd (2018)
EVALuna2:34971

THE PHYSIOLOGICAL FINGER JOINT ARCHITECTURE - AGE-RELATED INCREASE OF EROSIONS AND OSTEOPHYTES IN THE JOINTS OF HEALTHY INDIVIDUALS - Simon, David; Berlin, Andreas; Tascilar, Koray; Bayat, Sara; Engelke, Klaus; Rech, Jürgen; Figuereido, Camille; Hueber, Axel; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

The Urge for Mobile Apps in Rheumatology - a German Patient Perspective - Knitza, Johannes; Raab, Christina; Lambrecht, Antonia; Simon, David; Hagen, Melanie; Bayat, Sara; Schett, Georg; Kleyer, Arnd; Hueber, Axel (ARTHRITIS & RHEUMATOLOGY, 2019)
CRIS-Team WoS Importer:2020-02-07

TOPHUS RESOLUTION WITH PEGLOTICASE A PROSPECTIVE DUAL ENERGY COMPUTED TOMOGRAPHY STUDY - Schett, Georg; Araujo, E.; Bayat, Sara; Petsch, Christina; Englbrecht, Matthias; Faustini, F.; Kleyer, Arnd; Hueber, A.; Cavallaro, A.; Lell, Michael; Dalbeth, N.; Manger, Bernhard; et al. (2015)
EVALuna2:34461

Unveiling Metabolic Similarities of Entheses in Patients with Psoriasis and Psoriatic Arthritis Using Noninvasive In Vivo Molecular Imaging: Results From a Cross-sectional Exploratory Study - Fagni, Filippo; Tascilar, Koray; Noversa de Sousa, Rita; Bayat, Sara; Sollfrank, Lukas; Kleyer, Arnd; Sticherling, Michael; Regensburger, Adrian; Knieling, Ferdinand; Neurath, Markus; Schett, Georg; Waldner, Maximilian; et al. (Arthritis and Rheumatology, 2024)
Objective: We assessed and compared molecular tissue changes at the entheses in patients with psoriasis (PsO) and psoriatic arthritis (PsA) and in healthy controls (HCs) in vivo using multispectral optoacoustic tomography (MSOT) and described their relationship with clinical and ultrasound findings of enthesitis. Methods: A cross-sectional study (MSOT and Arthrosonography in PsA) in biologic disease-modifying antirheumatic drug–naïve patients with PsA and PsO and HCs was performed. Participants underwent clinical, ultrasonographic, and MSOT examination of six entheses (lateral humeral epicondyle, distal patellar tendon attachment, and Achilles tendon attachment). MSOT-measured hemoglobin (Hb), oxygen saturation (SO2), collagen, and lipid levels were quantified, and mean differences between groups were calculated using linear mixed effects models. MSOT-measured analytes were compared between entheses with and without clinical and ultrasound anomalies. Results: Ninety participants were included (30 PsO, 30 PsA, and 30 HCs), 540 entheses were clinically assessed, and 540 ultrasound and 830 MSOT scans were obtained. Patients with PsA and PsO showed increased oxygenated Hb (PsA: P = 0.003; PsO: P = 0.054) and SO2 (PsA: P < 0.001; PsO: P = 0.001) levels and decreased collagen signals (PsA: P < 0.001; PsO: P < 0.001) compared with HCs, with more pronounced changes in PsA. Significantly lower collagen levels (P = 0.01) and increased lipids (P = 0.03) were recorded in tender entheses compared with nontender ones. Erosions and enthesophytes on ultrasound were associated with significant differences in SO2 (P = 0.014) and lipid signals (P = 0.020), respectively. Conclusion: Patients with PsA and PsO exhibit an analogous metabolic pattern at the entheses that is exacerbated in the presence of inflammation. These findings support the notion of a psoriatic disease spectrum characterized by common immunometabolic tissue changes.
CRIS-Team Scopus Importer:2024-07-19

Update on imaging in gout: contrasting and comparing the role of dual-energy computed tomography to traditional diagnostic and monitoring techniques - Bayat, Sara; Baraf, H. S. B.; Rech, Jürgen (Clinical and Experimental Rheumatology, 2018)
In this systematic literature review, we update imaging modalities in gout, with a focus on newer technologies, particularly Dual-energy computed tomography (DECT). Conventional radiography (CR), ultrasonography (US), magnetic resonance imaging (MRI), computed tomography (CT) and dual-energy CT (DECT) have been used to evaluate different stages and clinical manifestations of gout and hyperuricaemia. We compare and contrast these modalities across the spectrum of this disease and of clinical scenarios and objectives (1).
EVALuna2:35013